Unintended asylum seekers: Bangladeshi probashi from Libya to Italy - Del Franco, Nicoletta (Migration Letters, 2021)
This paper focuses on Bangladeshi migrants, who have recently reached Italy from Libya. It discusses the results of field-work conducted between 2017 and 2018 with Bangladeshi asylum seekers living in the Parma area who are, or have been, hosted in emergency reception centers called CAS (Centri di Accoglienza Straordinaria). The aim of this paper is to explore the characteristics of this recent migration flow and to examine how migrants navigate the country’s formal reception system, adapting to and at the same time manipulating it. Migrants face a legal and political regime that is quite different from that of the 1990s and early 2000s. In order to secure refugee status, they find themselves caught up in a state-managed, complex reception system. Despite being in a weak and precarious position they move tactically in an unstable and uncertain environment to suit their life objectives.